2016
DOI: 10.1002/hbm.23248
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the spatiotemporal dynamics of processing task‐relevant and task‐irrelevant sound feature changes using concurrent EEG‐fMRI

Abstract: The cortical processing of changes in auditory input involves auditory sensory regions as well as different frontoparietal brain networks. The spatiotemporal dynamics of the activation spread across these networks has, however, not been investigated in detail so far. We here approached this issue using concurrent functional magnetic resonance imaging (fMRI) and electroencephalography (EEG), providing us with simultaneous information on both the spatial and temporal patterns of change‐related activity. We appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 77 publications
(99 reference statements)
2
15
0
Order By: Relevance
“…Per functional decoding of MAG 6 of both manual and automated annotations, MAG 6 is associated with visuospatial attention. This functional characterization is also supported by corresponding fronto-parietal activations that are often associated with attending to visual stimuli (Braga et al, 2016; Puschmann et al, 2016). MAGs 1 and 5 represent the perceptual processing streams of audiovisual information.…”
Section: Discussionmentioning
confidence: 61%
“…Per functional decoding of MAG 6 of both manual and automated annotations, MAG 6 is associated with visuospatial attention. This functional characterization is also supported by corresponding fronto-parietal activations that are often associated with attending to visual stimuli (Braga et al, 2016; Puschmann et al, 2016). MAGs 1 and 5 represent the perceptual processing streams of audiovisual information.…”
Section: Discussionmentioning
confidence: 61%
“…Since the early work by Cherry (1953), the sensory, cognitive, and neural processes contributing to solving this "cocktail party problem" have been investigated (McDermott, 2009;Anderson and Kraus, 2010;Rönnberg et al, 2013;Bidel-man and Dexter, 2015;Bronkhorst, 2015;Coffey et al, 2017). On the neural level, it has been shown that competing auditory streams are encoded individually at the level of the auditory cortex (Simon, 2015). Focusing attention selectively to one out of several competing sound streams results in an increased representation of the attended stream in the auditory cortex while simultaneously decreasing responses to the irrelevant input (Teder et al, 1993;Bidet-Caulet et al, 2007;Ross et al, 2010;Xiang et al, 2010;Power et al, 2011;Ding and Simon, 2012a;Mesgarani and Chang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the neural level, it has been shown that competing auditory streams are encoded individually at the level of the auditory cortex (Simon, 2015). Focusing attention selectively to one out of several competing sound streams results in an increased representation of the attended stream in the auditory cortex while simultaneously decreasing responses to the irrelevant input (Teder et al, 1993;Bidet-Caulet et al, 2007;Ross et al, 2010;Xiang et al, 2010;Power et al, 2011;Ding and Simon, 2012a;Mesgarani and Chang, 2012). Therefore, the attended stream dominates the ongoing auditory cortex activity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations